Inorganic Thin Film Deposition and Application on Organic Polymer Substrates. Issue 5 (28th November 2017) - Hora, Jitesh; Hall, Colin; Evans, Drew; Charrault, Eric
Abstract : This review details the emerging area of inorganic thin film coatings on polymer substrates, from examples of applications through to the fabrication processes and the underlying growth mechanism(s). Of particular focus is the use of physical vapor deposition to deposit thin metal and/or metal oxide films onto polymeric materials. This primary focus highlights an area of research, that is, gaining in popularity, as researchers attempt to provide insight into the adaption of a well‐established manufacturing process to be compatible with the ever expanding range of polymer substrates. The motivation for doing so comes from the evolution of existing industry (i.e., the semi‐conductor sector) to fabricate new devices (i.e., flexible electronics). In addition, the research challenges faced in achieving evaporated and sputtered thin film coatings on polymeric substrates, such as mechanical and thermal considerations will be discussed. Abstract : Regardless of chemistry, molecular weight and substrate type (thick solid polymer bulk, foil or thin layer deposited onto another substrate), the inherent properties of polymers present challenges throughout the whole PVD process. Overcoming these challenges and enhancing the resultant thin film performance is critical for the advancement of new technology, such as flexible electronics.